O efeito da espessura da chapa sobre a qualidade do reparo por atrito - Gontijo, Márcio Ferreira (2012)
The Friction Hydro Pillar Processing is friction welding process introduced in the early 90s. It is a solid-state welding process in which a hole is drilled and filled with a consumable rod of the same material. This method is capable of repairing long structure defects by a number of studs, welded sequentially along the defect, whereby a minimum in overlapping between two consecutive studs is assumed. This is a potential technique to repair steel structures in the offshore industry, since porosity and hydrogen embrittlementare strongly reduced in this process. In this work, the effects of the welded plate on the welding quality were studied. FHPP tests were carried out using steel plates of one, one and half and two inches. The axial stud load was 60 and 120 kN. The stud rotation was 1,400 and 1,700 rpm. Blocks studs and were machined out form ASTM A36 and AISI 1010 steels, respectively. The stud and base geometries were based on previous work conducted in the Laboratory for Friction and Wear Technology (LTAD). The block geometry was determined so that the block dimensions did not have any significant effect on the cooling rate. The welding tests were carried out using a welding system designed and built by LTAD. The unit consists of a hydraulic unit, a welding head and a control system. The unit is able to acquire and control the whole process according to the selected welding parameters. The main welding parameters are axial force, rotation, burn-off-length, forging force and duration. In order to evaluate the effects of the steel plate thickness on the cooling rate, thermocouples were welded close to the welding interface. The temperature as function of the time during the welding process for different plate thickness was acquired. The microstructure was characterized by using conventional metallographic techniques. The mechanical properties across the interface were evaluated by means hardness profiles. No welding defect was observed in metallographic sections for the selected welding parameters. Analysis of the effects of the welding plate thickness was complicated due to the fact that the selected welding plates showed chemical composition variations along their cross sections. Although, considering the equivalent carbon content it was possible to verify the effects of the plate thickness on the welding quality. It was observed that the higher the steel plate thickness the higher the cooling rate and the hardness.